Degradation of Humic Acids in Peat Water Using Fe3O4 Synthesized from Zircon Sand Tailing as Photo-Fenton Catalyst - Toepak, Erwin Prasetya; Pasaribu, Marvin Horale; Agnestisia, Retno; Elsandika, Gabriela (Jurnal Kimia Riset, 2025)
Zircon sand mining in Indonesia generates magnetic waste rich in magnetite (Fe₃O₄), which has semiconductor properties, making it an effective catalyst for degrading organic pollutants. This study explores the synthesis and application of Fe₃O₄ derived from zircon mining waste as a photo-Fenton catalyst for humic acid (HA) degradation in peat water. The Fe₃O₄ catalyst was synthesized using a co-precipitation method, confirmed by FTIR and XRD analyses. FTIR identified Fe–O bonds at 537 cm-1 and 419 cm-1, while XRD showed a spinel crystal structure with peaks at 2θ angles of 30.14°, 35.51°, 43.19°, and 56.96°. The catalytic activity was tested under UV light with varying H₂O₂ volumes and Fe₃O₄ masses. The optimized condition, using 0.03 g Fe₃O₄ and 1 mL H₂O₂, achieved a maximum HA degradation efficiency of 87.06% in 100 minutes. Kinetic analysis revealed second-order kinetics, with a rate constant (k) of 8.29 × 10-4 M-1.min-1 and R² = 0.9911, showing a strong correlation. The high efficiency is attributed to Fe₃O₄'s semiconductor properties, which facilitate hydroxyl radical formation and enhance electron transfer. These findings demonstrate the potential of Fe₃O₄ from zircon mining waste as a sustainable catalyst for environmental applications, particularly in treating organic pollutants in peat water.